2002
DOI: 10.1046/j.1439-0264.2002.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Biochemical Aspects of Apoptosis, Oncosis and Necrosis

Abstract: Recent investigations have demonstrated the need for a precise differentiation of various forms of cell death such as apoptosis, oncosis, necrosis and programmed cell death. Apoptosis is marked by cellular shrinking, condensation and margination of the chromatin and ruffling of the plasma membrane with eventually breaking up of the cell in apoptotic bodies. Cell death marked by cellular swelling should be called oncosis, whereas the term necrosis refers to the morphological alterations appearing after cell dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
334
1
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 456 publications
(355 citation statements)
references
References 49 publications
9
334
1
7
Order By: Relevance
“…delayed release may be due to the retained cell membrane integrity in early apoptotic cells, which is eventually lost during the later stages of apoptosis (49). In contrast to necrosis, many studies show that apoptosis is a "silent" process with regard to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…delayed release may be due to the retained cell membrane integrity in early apoptotic cells, which is eventually lost during the later stages of apoptosis (49). In contrast to necrosis, many studies show that apoptosis is a "silent" process with regard to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Fluopsin C induced ATP depletion, ROS generation and Δψ m collapse Several studies have suggested that ROS and cellular ATP play a pivotal role in determining whether cell death is apoptotic or oncotic [2,23,24] . Figure 8A shows that the cellular ATP content of MCF-7 cells in the presence and absence of fluopsin C was significantly decreased.…”
Section: Fluopsin C Destroyed the Cell Skeletonmentioning
confidence: 99%
“…Apoptosis and oncosis, two major forms of cell death, have distinct morphological and biochemical features [1,2] . Apoptosis is considered to be the major form of cell death in various physiological events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 27 cells were examined in each sample of the oAF, 23 in the iAF and a minimum of 13 cells in the NP. (a) Necrotic cells were identified when there was loss of integrity of the cell membrane and sometimes the nuclear membrane, together with swelling and vacuolisation of cell organelles and/or loss of organelle membranes [17,18]. (b) Apoptotic cells were identified by shrinking of the cell and blebbing of the cell membrane.…”
Section: Ultrastructural Studiesmentioning
confidence: 99%